2022
DOI: 10.1111/hex.13652
|View full text |Cite
|
Sign up to set email alerts
|

What are the reasons for unfinished nursing care as perceived by hospitalized patients? Findings from a qualitative study

Abstract: Introduction Unfinished nursing care (UNC), as the care required by patients that delayed or not delivered, has been investigated mainly from the perspective of nurses, while little is still known from the side of patients. Some studies have involved patients to measure which elements of care are mostly unfinished (e.g., mouth care), whereas a few studies have investigated the reasons for UNC as perceived by them. Their involvement in understanding the reasons for UNC is crucial to advance the kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…A total of 171 studies were identified and four were included [ 16 ] ( Figure 1 ). These were all primary studies ( Supplementary Material Table S4 )—three based on a qualitative design [ 20 , 21 , 22 ] and one based on a cross-sectional design with an open-ended final question [ 23 ]. The studies were conducted in Italy [ 20 , 21 ], Finland [ 22 ] and Iran [ 23 ] in acute hospital settings [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 171 studies were identified and four were included [ 16 ] ( Figure 1 ). These were all primary studies ( Supplementary Material Table S4 )—three based on a qualitative design [ 20 , 21 , 22 ] and one based on a cross-sectional design with an open-ended final question [ 23 ]. The studies were conducted in Italy [ 20 , 21 ], Finland [ 22 ] and Iran [ 23 ] in acute hospital settings [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…These were all primary studies ( Supplementary Material Table S4 )—three based on a qualitative design [ 20 , 21 , 22 ] and one based on a cross-sectional design with an open-ended final question [ 23 ]. The studies were conducted in Italy [ 20 , 21 ], Finland [ 22 ] and Iran [ 23 ] in acute hospital settings [ 20 , 21 , 22 ]. The perspectives investigated were those of both healthcare professionals [ 20 , 22 , 23 ] and patients [ 21 ] involving from 14 [ 22 ] to 29 [ 20 ] participants in the qualitative studies and 462 [ 23 ] in the quantitative one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, MNC may hurt nurses' job satisfaction (Al-Faouri et al, 2021). Thus, the healthcare literature has recently demonstrated a substantial and enduring interest in investigating the phenomenon of MNC (Chiappinotto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%